2014
DOI: 10.1186/1471-2164-15-s10-s2
|View full text |Cite
|
Sign up to set email alerts
|

Improving miRNA-mRNA interaction predictions

Abstract: BackgroundMicroRNAs are short RNA molecules that post-transcriptionally regulate gene expression. Today, microRNA target prediction remains challenging since very few have been experimentally validated and sequence-based predictions have large numbers of false positives. Furthermore, due to the different measuring rules used in each database of predicted interactions, the selection of the most reliable ones requires extensive knowledge about each algorithm.ResultsHere we propose two methods to measure the conf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
60
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(60 citation statements)
references
References 54 publications
0
60
0
Order By: Relevance
“…These findings reflect that the role of miRNA in T cell activation is spatiotemporal and numerous other factors are involved in their regulation 34 . This also underlines the fact that the miRNA target prediction tools like Targetscan, PicTar, miRanda are powerful but need to be experimentally validated in different disease states 35 …”
Section: Discussionmentioning
confidence: 78%
“…These findings reflect that the role of miRNA in T cell activation is spatiotemporal and numerous other factors are involved in their regulation 34 . This also underlines the fact that the miRNA target prediction tools like Targetscan, PicTar, miRanda are powerful but need to be experimentally validated in different disease states 35 …”
Section: Discussionmentioning
confidence: 78%
“…binding. These included transcripts not predicted as containing a miR-488-3p MRE, as expected from the high false negative rate of MRE prediction algorithms [32][33][34]. As expected, the two negative control transcripts, which are not responsive to Cerox1 transcript levels, and have no predicted MREs for miR-488-3p failed to bind miR-488-3p.…”
Section: Cerox1 Activity Is Mediated By Mir-488-3pmentioning
confidence: 64%
“…We used this stringent criterion to reduce probably false positive results. It is demonstrated that coding sequences and 5'UTR of genes can be targeted by miRNAs (Tabas-Madrid et al, 2014). However, in the present study, the 3'UTR of target genes were only applied for target prediction.…”
Section: Rna-seq and Micro Rna-seq Data Analysismentioning
confidence: 79%